(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the influence of parents in creating reading habits in children through positive examples and environmental support. This study uses a literature study method. The information used in this study was collected from various literature sources, such as books, papers, magazines, articles, journals, and theses related to this research topic. The data was analyzed in a qualitative descriptive manner. The results of the analysis show that by providing appropriate reading materials, making reading a daily routine, and providing fun motivation, parents can increase children’s interest in reading. Although challenges such as time constraints and the influence of technology can hinder these efforts, the positive impacts of reading habits, such as increased language skills, concentration, and imagination, provide long-term benefits for children’s development. Therefore, the role of parents is very vital in cultivating reading activities at home which will have a positive impact on children’s academic and emotional development